3D metrological characterization of functionally graded porous beta-titanium cellular structures to reproduce the complex internal human bone architecture (Transactions on Additive Manufacturing Meets Medicine, 2022)
The aim of this work is to evaluate the manufacturability of two functionally graded porose auxetic structures in a novel promising beta-Ti21S alloy by laser powder bed fusion (LPBF). The auxetic structure is selected thanks to the possibility to decrease Young's modulus by decreasing Poisson's ratio. The cell design parameters, namely the aspect ratio a / b and the angle q, affect the Poisson's ratio and the elastic modulus. Typical values of elastic modulus are in the range of 0.8 - 11 GPa and a yield stress between 7 to 280 MPa. Considering the humane bone, as an example the femur one, it is not characterized by a uniform porosity of the trabecular bone but rather by a variation depending on the position inside the bone. This is the reason of creating a functionally graded porous structure (FGPS) inside the auxetic structure. The two different auxetic unit cells selected in this work are characterized by an aspect ratio equal to 1.5 and angle q of 15 ° and 25 °, respectively. The porosity is obtained with three relative density, each one with three unit cells inside. In detail, auxetic FGPS with q equal to 15 ° is characterized by a relative density gradient of 0.34, 0.49, 0.66. Comparison between design and printed samples highlights an under sizing effect on strut thickness and pore size in both auxetic FGPSs due to deviations from ideal geometry that induce changes to the observed parameters as measured by CT imaging .
Keywords: Functionally graded porous structures; Auxetic; Titanium alloy; Metrological characterization; Laser powder bed fusion; additive manufacturing